Pelatihan Teknik Praktis Budidaya Jamur Tiram Sebagai Alternatif Protein Dan Penghasilan Tambahan Di Kelurahan Cempaka, Kota Banjarbaru - Lusiana, Herlina; Ambarwati, Riris; Fajriyanti, Ilisa; Ariani, Gusti Meinar Girda; Firdaus, Firdaus; Mursanto, Mursanto (Jurnal Pengabdian, 2024)
This activity aims to provide knowledge about oyster mushroom cultivation for the community in Gunung Kupang Village, Cempaka District, Banjarbaru. The implementation method in this community service activity is a method that includes counselling, providing understanding and assistance to the people of Gunung Kupang Village, Cempaka. The application of these methods is so that activity participants understand the practical techniques of oyster mushroom cultivation as an alternative protein and additional income. Activities The community service activities carried out by means of face-to-face meetings, discussions, which include training and counselling and empowerment went well. From this service activity, it appears that most of the participants do not know and understand how to practically cultivate oyster mushrooms as an alternative protein and additional income. to be able to increase income in the community of gunung kupang cempaka village. With this activity, the community is more motivated and active in increasing knowledge and production of oyster mushrooms.